Γδ T cells represent a major spontaneously cytotoxic cell population in the chicken. (August 2017) - Fenzl, Lisa; Göbel, Thomas W.; Neulen, Marie-Luise
Abstract: Natural killer cells in the chicken are mainly confined to the intestine, while only small frequencies are detectable in spleen, lung and blood. Here, we compared the spontaneous cytotoxicity of lymphocytes isolated from blood, spleen and intestine using a flow cytometric based cytotoxicity assay. There was no spontaneous cytotoxicity detected in chicken blood preparations. In contrast, freshly prepared splenocytes exhibited a spontaneous cytotoxicity of up to 50% and intestinal epithelial lymphocytes of up to 85%. This cytotoxicity was observed against the RP9 but not against the chicken CU24 target cell line. The observed cytotoxicity was MHC unrestricted since B 2 B 2 derived effector cells killed RP9 target cells (B 2 B 15 ) equally well compared to MHC mismatched 2D8 targets (B 19 B 19 ). The cytotoxicity of splenocytes was enhanced by preincubation with IL-2 or strongly increased with IL-2 plus IL-12. By cell sorting, we identified the CD8 + γδ T cell subset as the major effectors, whereas both CD8 − γδ T cells and CD8 + αβ T cells had only low cytolytic potential. Within intestinal lymphocyte CD45 + cells displayed cytotoxicity as well as sorted γδ T cells and NK cell. In conclusion, the chicken γδ T cells represent a major cytotoxic lymphocyte subset that can lyse target cells in a MHC unrestricted manner. Highlights: Chicken splenocytes and intestinal cells, but not PBL exhibit spontaneous cytotoxicity. This spontaneous cytotoxicity is mainly excerted by γδ T cells. In vitro stimulation with IL-2 and IL-12 increases the γδ T cell cytolytic capacity. Intestinal cells harbour two distinct cytolytic cell subsets, γδ T cells and NK cells.